2012
DOI: 10.1167/iovs.12-10701
|View full text |Cite
|
Sign up to set email alerts
|

Activity Limitation due to a Fear of Falling in Older Adults with Eye Disease

Abstract: PURPOSE.To examine whether patients with age-related macular degeneration (AMD), glaucoma, or Fuchs corneal dystrophy report limiting their activity due to a fear of falling as compared with a control group of older adults with good vision. METHODS.We recruited 345 patients (93 with AMD, 57 with Fuchs, 98 with glaucoma, and 97 controls) from the ophthalmology clinics of Maisonneuve-Rosemont Hospital (Montreal, Canada) to participate in a cross-sectional study from September 2009 until July 2012. Control patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(84 citation statements)
references
References 37 publications
3
79
1
1
Order By: Relevance
“…Two cross-sectional studies found that individuals with AMD have greater falls risk than those without53 and that fear of falling results in activity limitation 54. One case–control study55 used eye tracking and audio feedback while participants watched video simulations of walking through a building: AMD volunteers made more comments and more fixations than controls.…”
Section: Resultsmentioning
confidence: 99%
“…Two cross-sectional studies found that individuals with AMD have greater falls risk than those without53 and that fear of falling results in activity limitation 54. One case–control study55 used eye tracking and audio feedback while participants watched video simulations of walking through a building: AMD volunteers made more comments and more fixations than controls.…”
Section: Resultsmentioning
confidence: 99%
“…The disease may affect an elderly person's quality of life negatively, causing mobility limitations, 19 fear of falling, 20 and depressive symptoms. 21 The need for surgery depends on the severity of glaucoma, on the needs of the patient, and the likelihood that successful surgery will halt glaucoma progression and improve health-related quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…al. that FoF potentially mediates the relationship between vision loss and physical activity restriction [28]. In that study, the authors found that patients with AMD, Fuchs, and glaucoma were more likely to respond that they had restricted their activity as a result of FoF.…”
Section: Discussionmentioning
confidence: 99%
“…Studies using questionnaires to estimate level of physical activity such as the Short Form 36 (SF-36) Health Survey or the Yale Physical Activity Survey have shown that FoF is associated with a decrease in physical activity and physical health [2325]. To further study the association between vision and decreased physical activity [3, 26, 27], one prior study which sought to determine if FoF is a driver of physical activity restriction in individuals with vision loss found that those with eye disease were more likely to report activity restriction as a result of FoF than normally-sighted individuals [28]. This study, however, did not define whether the activities restricted related to physical activity or to other activities of daily living, and the study conclusions about mediation were based upon self-report of activity restriction alone.…”
Section: Introductionmentioning
confidence: 99%